Bentuk Bentuk Konflik dalam Organisasi - Agustin Nurkumalasari; Atiqotus Sya’adah; Fitriyatul Jannah; Nur Jannatul Muaffin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
Conflict is something that cannot be avoided in life. Throughout life, humans are always faced with and struggling with conflict. One dimension of conflict is conflict within the organization. Organization members are always faced with conflict. Within an organization, of course, sometimes there are differences of opinion, incompatibilities and contradictions which can give rise to many conflicts, ranging from small conflicts to large conflicts, both hidden and overt. The results of this research examine forms of conflict in organizations and conflict resolution strategies that focus on the context of Islamic education. Four types of conflict that often occur in an organization are, intrapersonal, interpersonal, intragroup, intraorganizational, and interorganizational. Furthermore, in the conflict resolution strategy there are five stages, namely, deliberation, third person intervention, confrontation, bargaining and compromise. The methodology in this research uses a literature review where all information obtained comes from relevant journals and books.